Surface sensing of quantum dots by electron spins - Moro, Fabrizio; Turyanska, Lyudmila; Wilman, James; Williams, Huw E.L.; Fielding, Alistair John; Patanè, Amalia (American Chemical Society, 2016)
The nanoscale design of quantum dots (QDs) requires advanced analytical techniques. However, those that are commonly used do not have sufficient sensitivity or spatial resolution. Here, we use magnetic resonance techniques combined with paramagnetic Mn-impurities in PbS QDs for sensitive probing of the QD surface and environment. In particular, we reveal inequivalent proton spin relaxations of the capping ligands and solvent molecules, strengths and anisotropies of the Mn-nuclear spin interactions, and Mn-nuclei distances with ~ 1 Å sensitivity. These findings demonstrate the potential of magnetically doped QDs as sensitive magnetic nano-probes and the use of electron spins for surface sensing.